2021
DOI: 10.3390/ma14164459
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Mechanical and Tribological Properties of Silicone-Based Composites Filled with Manganese Waste

Abstract: High-tonnage industrial processes generate high amount of waste. This is a growing problem in the whole world. Neutralizing such waste can be time consuming and costly. One of the possibilities of their reuse is to use them as fillers in polymer composites. Introduction of the filler in polymer matrix causes change in its mechanical and tribological properties. In the article, the effect of introducing fillers from post-production waste, and its effect on changing the physical properties of silicone-based comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…53 Mrówka et al found that adding manganese (II) oxide and manganese residue to silicone-based composites significantly improved the density, resilience, hardness, and tribological properties when compared to neat epoxy. 54 However, there are few research papers available on the material MnO 2 /epoxy nanocomposite. The tribological properties of MnO 2 /epoxy nanocomposite are also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…53 Mrówka et al found that adding manganese (II) oxide and manganese residue to silicone-based composites significantly improved the density, resilience, hardness, and tribological properties when compared to neat epoxy. 54 However, there are few research papers available on the material MnO 2 /epoxy nanocomposite. The tribological properties of MnO 2 /epoxy nanocomposite are also unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows that as the HNTs content increased from 2 to 6 phr, the temperature at 10% weight loss decreased from 437.2 ℃ to 435.3 ℃ and 434.4 ℃, the temperature at the maximum rate of degradation decreased from 466.9 ℃ to 464.1 ℃ and 463.3 ℃ and the final degradation temperature decreased from 495.1 ℃ to 488.9 ℃ and 487.2 ℃, respectively. With increased filler addition, there was an increase in residue [28]. Because of the gradual increase of polymer chain mobility, the presence and effectiveness of HNTs as a nanofiller could be linked to an increase in thermal stability [29].…”
Section: Thermal Properties Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
“…The Silesian University of Technology research using silicones as the composite matrices resulted in several results in which composites with organic and non-organic filling were tested. The study used inorganic zinc and manganese wastes from the steel industry as fillers in silicone-based composites [42,43].…”
Section: Introductionmentioning
confidence: 99%